1998
DOI: 10.1128/mcb.18.9.5140
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Protein Synthesis in Mammalian Cells with Codons Other Than AUG and Amino Acids Other Than Methionine

Abstract: Protein synthesis is initiated universally with the amino acid methionine. In Escherichia coli, studies with anticodon sequence mutants of the initiator methionine tRNA have shown that protein synthesis can be initiated with several other amino acids. In eukaryotic systems, however, a yeast initiator tRNA aminoacylated with isoleucine was found to be inactive in initiation in mammalian cell extracts. This finding raised the question of whether methionine is the only amino acid capable of initiation of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 59 publications
2
62
0
Order By: Relevance
“…The differential expression rates of ACC1 and HFA1 with the latter being extremely low may be due to this fact. Although eucaryotes and, in particular, yeast almost exclusively use AUG as an initiation codon, systematic studies with mutationally altered AUGs revealed that a series of alternative codons may initiate mammalian translation in vivo and in vitro (32,33). Also in yeast, codons other than AUG were effective when combined with either appropriately mutated initiator tRNAs or initiation factors (32,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential expression rates of ACC1 and HFA1 with the latter being extremely low may be due to this fact. Although eucaryotes and, in particular, yeast almost exclusively use AUG as an initiation codon, systematic studies with mutationally altered AUGs revealed that a series of alternative codons may initiate mammalian translation in vivo and in vitro (32,33). Also in yeast, codons other than AUG were effective when combined with either appropriately mutated initiator tRNAs or initiation factors (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…In particular with non-AUG initiation codons, specific nucleotides in the surrounding RNA context appear to be important determinants of initiation efficiency (35)(36)(37). In fact, some of the alternative initiation triplets identified in mammalian systems such as ACG, AUU, or AUA (33) are present within the HFA1 leader. It remains to be shown whether one of them acts, possibly together with an appropriate sequence context, as the in vivo initiation site of Hfa1p translation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been growing recognition of the use of alternate initiation codons in mammalian cells, often producing proteins with very different functions [39][40][41], as well as recognition of new mechanisms of translational control of protein structure and function [42,43]. Initiator codon mutations are uncommon, but typically they are associated with null alleles as no functional protein is produced [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two reports suggest that non-AUG codons are initiated with another amino acid than methionine. Using mutant tRNAs, it was shown that GUC and CAG can initiate protein synthesis in COS1 cells, respectively, with valine or glutamine (Drabkin and RajBhandary, 1998). It is therefore demonstrated, although in a manipulated situation, that initiation can occur in the absence of Met tRNA.…”
Section: Is Thementioning
confidence: 99%